Modern School Institution and Educational Writing - Magalhães, Justino (2016)
The modern school institution has shaped the education-institution. The construction and institutionalisation of the school have reflected institutional representation and modelling. School configurations have included symbology, materiality, curriculum, standards and pedagogy. Written culture, as the rational, method and order in the way of thinking and acting, has given support and meaning to the institutional representation of education and the school. It has enabled institutional schooling to correspond to education-institution in the modernisation of western society and within the context of the main reform movements. School reforms were changes in education. This essay presents a summary of the history of the educational institution and the representation of school. The structure of basic education accompanied the vernacular and was institutionalised through primary school. Secondary schooling was rooted in collegial tradition. It benefited from the Enlightenment Reforms of Minor Studies and the curriculum adjustment to new lettered profiles of the industrial revolution and the modernisation of public administration. Institutionalist theories are taken as the main epistemic framework.